Pengaruh Persepsi Kemudahan Penggunaan dan Persepsi Kepercayaan Terhadap Minat Bertransaksi Menggunakan Aplikasi OVO (Studi pada Mahasiswa S1 Manajemen Universitas Negeri Jakarta angkatan 2022-2023) - Rangga Triharto; Jerry Octavian; Ken Stevanous Widjaja; Rakha Athharsyah (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
This study aims to analyze the effect of trust and ease of use on the interest in transactions using the OVO application among S1 Management students of Universitas Negeri Jakarta, class of 2022-2023. Trust and ease of use are important factors in the adoption of digital financial technology. This research uses a quantitative approach with a survey method, involving 79 respondents from S1 Management students. The data were analyzed using multiple linear regression techniques to determine the extent of each variable's influence on transaction interest. The results show that both trust and ease of use have a positive and significant impact on the interest in transacting using the OVO application. These findings are expected to provide insights for fintech app developers to improve security features and user-friendliness, as well as support the development of fintech adoption among students. Keyword: Trust, Ease of use, Interest in transactions, OVO, Students, Fintech